The loss of human capital after the Spanish civil war - Blanca Sánchez-Alonso; Carlos Santiago-Caballero (European Historical Economics Society (EHES), 2021)
Forced migrations and exiles are shocks that affect to the lives of millions of individuals. Among the consequences of this non-voluntary migration, the loss of a significant stock of human capital is of particular importance. The Republican exile in post-civil war Spain is an excellent case study since the traditional representation is that Spain lost highly qualified population. However, not that much has been said about the quantification of this loss or the measurement of the quality of the human capital that left Spain after the end of the civil war. This paper tries to fill this gap offering an estimation of the quality of the human capital that left Spain comparing it with the years that preceded and followed it and with economic migrants who were moving at the same time. Mexico was the major destination for Spanish refugees since the beginning of the Civil War and produced a unique primary source for analysing economic immigrants and refugees. We use multivariable regression models to estimate the existence of a skill premium in Republican refugees, analysing proxies of human capital like occupations, heights, and foreign languages spoken. Our results suggest that Spanish Republican refugees presented a skill premium compared to economic migrants. This result is particularly relevant because traditional economic migrants from Spain to Mexico have been considered a "privileged migration" given their high levels of human capital. The quality of the source allows us to extend the analysis to women human capital, an important contribution given the traditional invisibility of women in recorded economic history.
Keywords: N36; J24; J61; 330; Human Capital; Refugees; Spanish Civil War